2013
DOI: 10.1371/journal.pone.0058746
|View full text |Cite
|
Sign up to set email alerts
|

Spry1 and Spry4 Differentially Regulate Human Aortic Smooth Muscle Cell Phenotype via Akt/FoxO/Myocardin Signaling

Abstract: BackgroundChanges in the vascular smooth muscle cell (VSMC) contractile phenotype occur in pathological states such as restenosis and atherosclerosis. Multiple cytokines, signaling through receptor tyrosine kinases (RTK) and PI3K/Akt and MAPK/ERK pathways, regulate these phenotypic transitions. The Spry proteins are feedback modulators of RTK signaling, but their specific roles in VSMC have not been established.Methodology/Principal FindingsHere, we report for the first time that Spry1, but not Spry4, is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 36 publications
(40 reference statements)
4
49
0
Order By: Relevance
“…When PI3K is activated, it generates a second messenger in the cell membrane: PIP 3 , which binds to and activates Akt. Akt, also known as protein kinase B (PKB), has a relatively large molecular mass of 60,000 Da and phosphorylates a variety of transcription factors directly and can therefore inhibit apoptosis gene expression and enhance the anti-apoptotic gene expression, thereby promoting cell survival [1,26]. In the present study, we first confirmed that the Ox-LDL-mediated proliferation was via the PI3K/ Akt and MAPK/ERK pathways.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…When PI3K is activated, it generates a second messenger in the cell membrane: PIP 3 , which binds to and activates Akt. Akt, also known as protein kinase B (PKB), has a relatively large molecular mass of 60,000 Da and phosphorylates a variety of transcription factors directly and can therefore inhibit apoptosis gene expression and enhance the anti-apoptotic gene expression, thereby promoting cell survival [1,26]. In the present study, we first confirmed that the Ox-LDL-mediated proliferation was via the PI3K/ Akt and MAPK/ERK pathways.…”
Section: Discussionsupporting
confidence: 67%
“…The mechanisms of Ox-LDL-induced macrophage proliferation are complex and include processes such as an increase in intracellular calcium, activation of protein kinase C (PKC), and secretion of granulocyte-macrophage colony-stimulating factor (GM-CSF) [35][36][37]. PI3K/Akt and MAPK/ERK are believed to be involved in downstream signaling [4,26,38]. The MAPK signaling pathway includes ERK, JNK and p38 MAPK; the ERK pathway is the most common cell proliferative response-mediated signaling pathway [1,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat carotid artery injury model, treatment of injured vessels with a chimeric protein consisting of the HIV TAT membrane translocation sequence and Spry2 (TAT-hSpry2) inhibited neointima formation and VSMC proliferation for up to 28 days post injury [72]. Furthermore, in vitro studies on VSMC show that Spry1 and Spry4 have different roles in VSMC phenotypic modulation; Spry1 maintains the VSMC contractile phenotype in part by regulating an Akt/FoxO/myocardin pathway [59]. Together, these data show that Spry family members function to maintain proper levels of RTK signaling during vascular development, the vascular response to injury and vascular homeostasis.…”
Section: Fgf Signaling In Endothelial Cells Angiogenesis and Neovasmentioning
confidence: 99%
“…Yang et al reported that FOXO3a regulates the gene transcription of myocardin, which participates in VSMC phenotypic modulation [16]. FOXO3a and its downstream gene, apoptotic protease activating factor 1, play important roles in VSMC survival during vessel remodeling and atherogenesis [17].…”
Section: Introductionmentioning
confidence: 99%